Exploiting Erasmus : the Erasmian legacy and religious change in early modern England - Dodds, Gregory D. (Erasmus studies., 2009)
Exploiting Erasmus examines the legacy of Erasmus in England from the mid-sixteenth century to the overthrow of James II in 1688 and studies the various ways in which his works were received, manipulated, and used in religious controversies that threatened both church and state.